Rekonstruksi Hak Keperdataan Anak Luar Kawin: dari Perlindungan Nasab ke Perlindungan Hak Anak - Hamka Husein Hasibuan; Pagar; Hasan Matsum; Fauziah Lubis (Al Fuadiy Jurnal Hukum Keluarga Islam, 2026)
Children born out of wedlock constitute a complex legal and social issue, particularly in relation to the fulfillment of civil rights within plural legal systems. In Indonesia, the regulation of such rights reflects an ongoing tension between positive law, which increasingly emphasizes child protection, and Islamic law, which prioritizes the preservation of lineage (nasab). This article examines the construction of civil rights of children born out of wedlock under Indonesian positive law and Islamic law, with particular attention to lineage, guardianship, inheritance, and maintenance. Using a normative legal method with statutory, conceptual, and comparative approaches, the discussion highlights the impact of Constitutional Court Decision No. 46/PUU-VIII/2010 in reshaping the legal relationship between children born out of wedlock and their biological fathers. The findings indicate that positive law has shifted toward a child-centered paradigm by allowing civil relations based on scientific proof, while Islamic law maintains normative restrictions rooted in the sanctity of lawful marriage. Despite these differences, both legal systems share a common commitment to safeguarding the welfare and dignity of children. The article contributes to legal discourse by mapping points of convergence and divergence between the two systems and offering a balanced understanding of how child protection and moral-legal principles interact within Indonesia’s family law framework.